Mediating role of depression medication on association between Body Mass Index and cigarette smoking among US adults: Insights from the NHIS - Olanrewaju Onigbogi; Alperen Korkmaz; Kebba Kah; Emilee J. Delbridge; Kolawole Okuyemi (PLoS ONE, 2026)
Depression in people who are obese, and smoke cigarettes is often complicated by the possibility of using smoking as a tool for coping with stress. This study sought to determine the mediating role of depression medication on smoking among obese, overweight, normal weight and underweight adults. Data from the 2023 National Health Interview Survey, an annual public health survey of adults from 18–65 years of age in the United States of America, was analyzed using a Generalized Structural Equation Model. Underweight participants on depression medication were more likely to smoke compared to obese participants (reference group: obese; aOR = 0.49, 95% CI: [0.38, 0.63]). There was an indirect association between obesity and depression medication on smoking and obese participants on depression medication had 1.32 times higher odds of smoking when using depression medication compared to underweight individuals (aOR = 1.32, 95% CI: [1.09, 1.56]). Use of depression medication had the highest mediating role on smoking among underweight and the lowest role among obese participants (aOR = 1.64, 95% CI: [1.05, 2.22]). The findings suggest that body mass index should be considered in planning smoking cessation interventions in health care settings.